Filtered asymmetric dark matter during the Peccei-Quinn phase transition - M. Ahmadvand (Journal of High Energy Physics, 2021)
Abstract In this paper, we propose a bubble filtering-out mechanism for an asymmetric dark matter scenario during the Peccei-Quinn (PQ) phase transition. Based on a QCD axion model, extended by extra chiral neutrinos, we show that the PQ phase transition can be first order in the parameter space of the model and regarding the PQ symmetry breaking scale, the mechanism can generate PeV-scale heavy neutrinos as a dark matter candidate. Considering a CP-violating source, during the phase transition, discriminating between the neutrino and antineutrino number density, we find the observed dark matter relic abundance, such that the setup can be applied to the first order phase transition with different strengths. We then calculate effective couplings of the QCD axion addressing the strong CP problem within the model. We also study the energy density spectrum of gravitational waves generated from the first order phase transition and show that the signals can be detected by future ground-based detectors such as Einstein Telescope. In particular, for a visible heavy axion case of the model, it is shown that gravitational waves can be probed by DECIGO and BBO interferometers. Furthermore, we discuss the dark matter-standard model neutrino annihilation process as a source for the creation of PeV-scale neutrinos.